2018
DOI: 10.1017/jfm.2018.132
|View full text |Cite
|
Sign up to set email alerts
|

Combined free-stream disturbance measurements and receptivity studies in hypersonic wind tunnels by means of a slender wedge probe and direct numerical simulation

Abstract: Combined free-stream disturbance measurements and receptivity studies in hypersonic wind tunnels were conducted by means of a slender wedge probe and direct numerical simulation. The study comprises comparative tunnel noise measurements at Mach 3, 6 and 7.4 in two Ludwieg tube facilities and a shock tunnel. Surface pressure fluctuations were measured over a wide range of frequencies and test conditions including harsh test environments not accessible to measurement techniques such as pitot probes and hot-wire … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…works [28,31,34], as described in Section I. Moreover, in the work of Wagner et al [48] low frequencies (below 100 kHz) were found to have a significant effect on the response to slow acoustic waves, which was more amplified compared to the higher frequencies. Figures 13 and 14 show the time-averaged surface heat flux (in kW/m 2 ) for fast and slow acoustic waves respectively.…”
Section: Laminar Base Flow Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…works [28,31,34], as described in Section I. Moreover, in the work of Wagner et al [48] low frequencies (below 100 kHz) were found to have a significant effect on the response to slow acoustic waves, which was more amplified compared to the higher frequencies. Figures 13 and 14 show the time-averaged surface heat flux (in kW/m 2 ) for fast and slow acoustic waves respectively.…”
Section: Laminar Base Flow Resultsmentioning
confidence: 93%
“…[47] and Wagner et al [48], aimed at investigating the noise characteristics in the environment of hypersonic wind tunnels.…”
Section: Introductionmentioning
confidence: 99%
“…The geometry consists of a cylinder-wedge shaped wall boundary, with a nondimensional nose radius of R = 1 and a half-wedge angle of 4 • , based on the wedge probe investigated in Wagner et al (2018). The main dimensions (normalised with the nose radius) of the three-dimensional computational domain, shown in figure 1(a), are L x = 1000 along the x-axis, L y = 352 along the y-axis and L z = 55 along the z-axis.…”
Section: Computational Domainmentioning
confidence: 99%
“…For the specific case of hypersonic wind tunnels, it is known from previous studies, e.g. Duan et al (2014), Wagner et al (2018) and Cerminara et al (2019), that slow acoustic waves are likely to be the most dominant acoustic disturbance radiated from the turbulent boundary layer on the nozzle wall. This does not mean, however, that fast modes are not of interest.…”
Section: Disturbance Growth and Breakdown Mechanismmentioning
confidence: 99%
See 1 more Smart Citation